The Influence of Audit Committee, Institutional Ownership, and Audit Quality on Accounting Conservatism in Conventional Banks Listed on The Indonesia Stock Exchange 2022–2024 - Miftahul Jannah; Sri Rahayu; Fredy Olimsar (Siber Nusantara of Economic and Finance Review, 2026)
This study investigates the impact of the audit committee, institutional ownership, and audit quality on accounting conservatism in conventional banks listed on the Indonesia Stock Exchange (IDX) during 2022–2024. Based on agency and signaling theories, governance mechanisms are expected to reduce managerial opportunism and encourage more conservative financial reporting. Using a quantitative descriptive method with exhaustive sampling, the study includes 43 banks, resulting in 129 observations, which were reduced to 125 after outlier removal. Multiple linear regression analysis reveals that the audit committee has a significant negative effect on accounting conservatism, indicating that a larger committee does not necessarily improve oversight effectiveness. Meanwhile, institutional ownership and audit quality show no significant influence, suggesting that ownership proportion and external auditors do not directly determine conservative accounting practices. However, all variables jointly have a significant effect, with a significance level of 0.017 and an adjusted R-squared of 5.8%. These findings enrich the understanding of corporate governance and accounting conservatism in Indonesia’s banking sector, particularly in the post-pandemic context.